Diagenetic processes imprint on reservoir quality and hydraulic flow units of the lower Cretaceous strata (Fahliyan Formation), Izeh and Dezful Zones, Zagros Basin, SW Iran - Rostamtabar, Mohammad; Khanehbad, Mohammad; Mahboubi, Asadollah; Mahmudy-Gharaie, Mohamad Hosein; Hajian-Barzi, Mahmoud (Journal of petroleum science and technology, 2024)
The Fahliyan Formation, a significant carbonate reservoir in southwestern Iran encompassing the Izeh and Dezful Zones, underwent detailed petrographic investigations. These analyses revealed eight distinct microfacies associated with four different depositional settings within a homoclinal ramp model. From a diagenesis perspective, the formation has undergone various processes, including micritization, dissolution, compaction, cementation, dolomitization, stylolitization, and fracturing. These diagenetic features affected the Fahliyan Formation from early marine–meteoric to late burial diagenetic realms. Notably, dissolution developed as the most effective and widespread diagenetic feature, improving reservoir quality. Likewise, fracture and dolomitization positively impact reservoir quality, while compaction and cementation have destructive effects. Micritization and early isopachous calcite cement have a retentive role in reservoir characteristics. In addition, the Flow Zone Indicator (FZI) approach introduced three Hydraulic Flow Units (HFUs). The correlation between microfacies types and their petrophysical features indicates that the bioclastic peloid packstones and grainstones have better reservoir quality, which resulted from dissolution, and initial isopachous calcite cements. Also, Planktonic foraminifer’s bioclastic mud/ wackestone and Quartz-bearing mudstone, equivalent to HFU1, indicate lower reservoir quality due to the compaction (stylolitization) and cementation.